3D Numerical Modeling of Water–Rock Coupling Heat Transfer Within a Single Fracture - He, Yuanyuan; Bai, Bing; Cui, Yinxiang; Lei, Hongwu; Li, Xiaochun (International journal of thermophysics, 2020)
Understanding working fluids flow and heat transfer in Enhanced Geothermal System (EGS) is critically important for assessing production capabilities and heat extraction rates from hot dry rock (HDR) effectively. Water is a conventional working fluid of EGS; therefore, it is necessary to study water–rock coupling heat transfer within HDR fractures. A single fracture is a basic element of complex fracture systems of EGS, so there has been many researches investigating water flow and heat transfer through a single fracture within a cylindrical HDR specimen for preliminary study, and heat transfer coefficient (HTC) is often adopted to evaluate heat transfer performance between water and rock, but there is a lack of knowledge about the inner surface temperature ( T i ), which is a key parameter to calculate HTCs, due to limitations of current experimental methods and analytical solutions. Numerical modeling can be an alternative way to help us have a more comprehensive understanding of the distributions of T i , but the 2D numerical models only reveal the distribution of T i along the flow direction without its distribution perpendicular to the flow direction, namely, the distribution along radius. Therefore, it is essential to conduct the corresponding 3D numerical modeling to obtain the radial distribution of T i . In this paper, a 3D numerical model accounting for surface morphology is proposed to simulate water flow and heat transfer through a single fracture within a cylindrical HDR specimen and verified by experimental data. The results reveal that the radial distribution of T i can be described by a quadratic function mostly, and neither the surface morphology nor the phase state has influence on the tendency of T i . Finally, four relatively stable formulas to calculate HTCs so far are compared and discussed.